2015
DOI: 10.1371/journal.pone.0136372
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Genetic Analysis of Complement 3 Gene and Schizophrenia

Abstract: Complement pathway activation was found to occur frequently in schizophrenia, and complement 3 (C3) plays a major role in this process. Previous studies have provided evidence for the possible role of C3 in the development of schizophrenia. In this study, we hypothesized that the gene encoding C3 (C3) may confer susceptibility to schizophrenia in Han Chinese. We analyzed 7 common single nucleotide polymorphisms (SNPs) of C3 in 647 schizophrenia patients and 687 healthy controls. Peripheral C3 mRNA expression l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
(44 reference statements)
2
10
0
Order By: Relevance
“…A preliminary investigation on the association of 5 SNPs (rs2277984, rs7951, rs11672613, rs2230205, and rs2230199) in C3 with SCZ found no significant association between these SNPs and SCZ [16]. In our study, we increased the number of subjects and studied the association of 10 tag SNPs (rs11569562, rs344555, rs2241393, rs2241392, rs11569514, rs445750, rs451760, rs11672613, rs2230205, and rs2250656) in C3 with SCZ.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A preliminary investigation on the association of 5 SNPs (rs2277984, rs7951, rs11672613, rs2230205, and rs2230199) in C3 with SCZ found no significant association between these SNPs and SCZ [16]. In our study, we increased the number of subjects and studied the association of 10 tag SNPs (rs11569562, rs344555, rs2241393, rs2241392, rs11569514, rs445750, rs451760, rs11672613, rs2230205, and rs2250656) in C3 with SCZ.…”
Section: Discussionmentioning
confidence: 86%
“…Due to the importance of C3 in multiple immunoregulatory processes, the investigation of C3 polymorphisms remains of interest in SCZ research. However, a handful of genetic studies have been performed to study the association between single nucleotide polymorphisms (SNPs) in C3 and SCZ, but no significant association has been discovered [16]. In this study, we selected 10 SNPs of C3 (rs11569562, rs344555, rs2241393, rs2241392, rs11569514, rs445750, rs451760, rs11672613, rs2230205, and rs2250656) to examine the association between C3 variation and SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…First, the lack of a significant association between rs1064395 and schizophrenia may be caused by the modest sample size, possibly resulting in a type II error 44. Accordingly, our findings should be considered only preliminary and will require further investigations for validation in independent samples.…”
Section: Discussionmentioning
confidence: 95%
“…48 Also at the molecular level, the gene encoding C3 has been reported to be a genetic schizophrenia susceptibility region, 49 whereas others could not confirm this. 50 In SLE patients data are limited. Pego-Reigosa et al reported low C3 levels in 4/10 patients with lupus psychosis and no other complement alterations were found.…”
Section: Discussionmentioning
confidence: 99%